A laser-weldable high-blackness halogen-free flame-retardant glass fiber reinforced PA6 material and preparation method thereof

By adding specific laser penetration agents and optimized processes to the halogen-free flame-retardant glass fiber reinforced PA6 material, the problem of low laser penetration in traditional materials is solved, and a black material with high laser transmissibility and excellent mechanical properties is achieved, which is suitable for laser welding.

CN115850959BActive Publication Date: 2025-03-14XUZHOU TENGFEI ENG PLASTICS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211580777.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-09
Publication Date
2025-03-14
Estimated Expiration
2042-12-09

AI Technical Summary

Technical Problem

The traditional black halogen-free flame-retardant glass fiber reinforced PA6 material cannot meet the requirements of laser welding due to the extremely low laser penetration rate during laser welding.

Method used

A specific formula of high-black halogen-free flame retardant glass fiber reinforced PA6 material contains PA6 resin, glass fiber, halogen-free flame retardant, laser penetrants A and B, antioxidants, lubricants, flow agents and toners. By optimizing the aspect ratio and partition weightless feeding of the twin-screw extruder, the laser transmittance of the material is enhanced.

Benefits of technology

It realizes the high laser transmissibility and excellent mechanical properties of the material, and is suitable for black materials for laser welding, improving the laser welding effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003990541860000031
    Figure BDA0003990541860000031
  • Figure BDA0003990541860000051
    Figure BDA0003990541860000051
Patent Text Reader

Abstract

A laser-weldable high-blackness halogen-free flame-retardant glass fiber reinforced PA6 material and a preparation method thereof, the material comprises the following components in percentage by mass: PA6 resin 26.9-45.4%, glass fiber 25-35%, halogen-free flame retardant 16-18%, laser penetrant A 10-20%, laser penetrant B 3-5%, antioxidant 0.1-0.3%, lubricant 0.5-0.6%, flow agent 0.4-0.6%, toner 0.2-2%; PA6 resin, two laser penetrants, and toner are put into a high-mixer, and then an auxiliary agent is added to obtain a mixed main material A, and the mixed main material A is put into the main feeding hopper of a twin-screw extruder; the halogen-free flame retardant and glass fiber are respectively added to the weight-loss feeding hoppers of the second heating zone and the fourth heating zone; the extruded material strip is cooled, pelletized, and dried to obtain a finished product. The preparation process is green, simple, and low-cost, and the obtained PA6 material has high strength and high laser transmittance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and specifically relates to a laser-weldable high-blackness halogen-free flame-retardant glass fiber reinforced PA6 material and a preparation method thereof. Background Art

[0002] Polyamide (PA, commonly known as nylon) is the most widely used and most diverse type of polymer material in the engineering plastics industry. Among them, PA66 and PA6 in the aliphatic polyamide family are the two with the largest output in the entire polyamide family, accounting for more than 60% of the entire polyamide production capacity. PA6 has the advantages of self-lubricity, excellent wear resistance and processing fluidity, good chemical resistance and fatigue resistance, especially after fiber reinforcement, the overall rigidity and modulus of the material will be increased by 2-3 times. It is widely used in automotive parts, electronic appliances, rail transportation, sports equipment, medical equipment, high-voltage transmission equipment and other fields.

[0003] With the increasing proportion of lightweight automobiles and new energy automobile plastic parts, flame-retardant glass fiber reinforced PA materials are becoming more and more popular in automobile circuit equipment and battery replacement systems due to their excellent mechanical strength and flame retardant properties, good processing fluidity and dimensional stability. For example, the housing of the automobile igniter, the frame of the battery module of new energy vehicles, etc., in addition to requiring the material to have a high rigidity and toughness balance, it is more important to have high flame retardancy and reliability in harsh environments. The traditional bromine-based flame retardant system has been strongly resisted due to problems such as large smoke production and the generation of toxic gases. The new halogen-free flame retardant can well solve the problem of environmentally unfriendly materials.

[0004] The traditional welding methods of thermoplastic resins mainly include hot pressing welding, vibration welding and ultrasonic welding. The main disadvantages of these welding methods are high noise, high welding shavings and low welding strength, which are not suitable for welding precision plastic parts. With the integration of new energy vehicle circuit board modules, the capacitor components that were originally scattered in different modules will now be concentrated in one module group. The centralization of parts increases the difficulty of welding between module groups. Traditional ultrasonic waves can no longer meet the welding requirements of products. Laser welding is a welding technology that uses a high-energy-density laser beam as a heat source. The laser passes through the laser penetration layer and is reflected and absorbed by the laser absorption layer. The heat is concentrated and melted at the interface between the penetration layer and the absorption layer. The light-absorbing layer and the light-transmitting layer are tightly fused together through the applied pressure. Laser welding has the advantages of excellent welding appearance, high welding strength, and no welding shavings. It is very suitable for welding precision plastic parts. Carbon black, as a traditional dye, dyes the light-absorbing layer black, and its laser penetration rate is extremely low. Coupled with the addition of glass fiber and a large amount of halogen-free flame retardants, the laser penetration rate of the light-absorbing layer is almost zero. The laser penetration rate of the traditional black halogen-free flame-retardant glass fiber reinforced PA6 as the light-absorbing layer material is almost impossible to meet the requirements of laser welding. Therefore, it is particularly important to develop a high-black halogen-free flame-retardant glass fiber reinforced PA6 material suitable for laser welding. Summary of the invention

[0005] The purpose of the present invention is to provide a high-blackness halogen-free flame-retardant glass fiber reinforced PA6 material that can be laser welded and a preparation method thereof. The preparation process of the method is green, simple and low-cost. The prepared PA6 material has high strength and high laser transmittance, can be applied to black materials that require laser welding and can improve the laser welding effect.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] A laser-weldable high-blackness halogen-free flame-retardant glass fiber reinforced PA6 material, comprising the following components in percentage by mass: PA6 resin 26.9-45.4%, glass fiber 25-35%, halogen-free flame retardant 16-18%, laser penetrant A 10-20%, laser penetrant B 3-5%, antioxidant 0.1-0.3%, lubricant 0.5-0.6%, flow agent 0.4-0.6%, toner 0.2-2%;

[0008] The relative viscosity of the PA6 resin is 2.0-2.8;

[0009] The glass fiber is an alkali-free chopped glass fiber with a single filament diameter of 7-15 μm;

[0010] The halogen-free flame retardant is an organophosphorus flame retardant;

[0011] The laser penetrant A is semi-aromatic nylon or long carbon chain nylon; the semi-aromatic nylon is one or two of PA6I and PA6T; the long carbon chain nylon is at least one of PA1010, PA1212 and PA610;

[0012] The laser penetrant B is semi-aromatic nylon, and the semi-aromatic nylon is PA6T or PA9T;

[0013] The antioxidant is at least one of a hindered phenol antioxidant, a phosphite antioxidant, an inorganic phosphate antioxidant, and an organic copper salt antioxidant;

[0014] The lubricant is at least one of stearates, silicones, and ethylene bis stearamides;

[0015] The flow agent is at least one of low molecular weight polyethylene wax and hyperbranched polyester;

[0016] The toner is prepared by mixing organic three primary color toners, and the toner appears black.

[0017] Preferably, the relative viscosity of the PA6 resin is 2.8.

[0018] Preferably, the glass fiber is an alkali-free chopped glass fiber with a single fiber diameter of 13 μm.

[0019] Preferably, the laser penetrant A is semi-aromatic nylon, and the semi-aromatic nylon is PA6I; and the laser penetrant B is PA6T.

[0020] Preferably, the antioxidant is an inorganic phosphate antioxidant; the antioxidant is Brueggemann H10.

[0021] Preferably, the lubricant is ethylene bis stearic acid amide.

[0022] The present invention also provides a method for preparing a laser-weldable high-blackness halogen-free flame-retardant glass fiber reinforced PA6 material, comprising the following steps:

[0023] (1) Prepare the raw materials according to the following components:

[0024] PA6 resin 26.9-45.4%, glass fiber 25-35%, halogen-free flame retardant 16-18%, laser penetrant A 10-20%, laser penetrant B 3-5%, antioxidant 0.1-0.3%, lubricant 0.5-0.6%, flow agent 0.4-0.6%, color powder 0.2-2%;

[0025] (2) PA6 resin, laser penetrant A, laser penetrant B, and color powder are pre-mixed in a high-speed mixer according to a certain proportion, the speed is set to 500 r / min, and the mixture is mixed for 2-4 minutes to obtain a mixture, and then an antioxidant, a lubricant, and a flow agent are respectively added to the mixture, the speed is set to 500 r / min, and the mixture is mixed for 2-4 minutes to obtain a mixed main material A, and finally the mixed main material A is added to the main feeding hopper of the twin-screw extruder; the halogen-free flame retardant is added to the weight-loss feeding hopper of the second heating zone according to a proportion; and the glass fiber is added to the weight-loss feeding hopper of the fourth heating zone according to a proportion;

[0026] (3) The temperature of each section of the 8 extrusion zones of the twin-screw extruder is set as follows: 200-200°C for zone 1, 230-250°C for zone 2, 230-250°C for zone 3, 230-240°C for zone 4, 230-250°C for zone 5, 230-240°C for zone 6, 220-230°C for zone 7, 220-230°C for zone 8, and 230-250°C for die head; the main engine speed of the twin-screw extruder is set at 300-400r / min, and auxiliary vacuum systems are set in zones 3 and 6, and the vacuum degree of the auxiliary vacuum systems is set to be higher than 0.06Mpa. After the extruded material strips are cooled, pelletized, and dried to obtain the finished product.

[0027] Preferably, in step (2), the screw length-to-diameter ratio of the twin-screw extruder is (35-42):1.

[0028] Compared with the prior art, the present invention uses an organic phosphorus flame retardant with a special structure, which has little effect on the laser permeability of the material; optimizes the aspect ratio of the twin-screw extruder and adopts partitioned weightless feeding to avoid the weakening of the mechanical properties and flame retardancy of the material due to uneven proportions of concentrated feeding components and poor mixing effect; double vacuum partitioned devolatilization maximizes the laser transmittance of the material; the optimized process route combined with the formula optimization of each embodiment can obtain a glass fiber reinforced halogen-free flame-retardant laser welding PA6 material with high laser transmittance and excellent mechanical properties. The preparation process of the present invention is green, simple, and low-cost. The prepared PA6 material has high strength and high laser transmittance, can be applied to black materials that require laser welding, and can improve the laser welding effect. DETAILED DESCRIPTION

[0029] The present invention is further described in detail below in conjunction with specific examples and comparative examples.

[0030] The formulations of Examples 1-5 and Comparative Examples 1-3 are shown in Table 1 below:

[0031] Table 1 Formulations of Examples 1-5 and Comparative Examples 1-3

[0032]

[0033]

[0034] In Examples 1-3, the relative viscosity of the PA6 resin is 2.8; the glass fiber is an alkali-free chopped glass fiber with a monofilament diameter of 13 μm; the halogen-free flame retardant is an organic phosphorus flame retardant, namely Zhejiang Chuanhua Chemical Halogen-Free Flame Retardant 9101-1; the laser penetrant A is PA6I; the antioxidant is Brüggemann H10; the lubricant is ethylene bis stearic acid amide EBS; the flow agent is SH2303 of Dongguan Sanhe Chemical Co., Ltd.; the color powder is a mixture of organic three primary color powders, and the color powder appears black.

[0035] In Examples 4-5, the relative viscosity of the PA6 resin is 2.8; the glass fiber is an alkali-free chopped glass fiber with a monofilament diameter of 13 μm; the halogen-free flame retardant is an organic phosphorus flame retardant, namely Zhejiang Chuanhua Chemical Halogen-Free Flame Retardant 9101-1; the laser penetrant APA6I; the laser penetrant B is PA6T; the antioxidant is Brüggemann H10; the lubricant is ethylene bis stearic acid amide EBS; the flow agent is SH2303 of Dongguan Sanhe Chemical Co., Ltd.; the color powder is a mixture of organic three primary color powders, and the color powder appears black.

[0036] In Comparative Example 1, the relative viscosity of the PA6 resin is 2.8; the glass fiber is an alkali-free chopped glass fiber with a monofilament diameter of 13 μm; the halogen-free flame retardant is an organic phosphorus flame retardant, namely, Zhejiang Chuanhua Chemical Halogen-Free Flame Retardant 9101-1; the laser penetrant A is PA6I; the laser penetrant B is PA6T; the antioxidant is Brüggemann H10; the lubricant is ethylene bis stearic acid amide EBS; the flow agent is SH2303 of Dongguan Sanhe Chemical Co., Ltd.; and the color powder is carbon black.

[0037] In Comparative Example 2, the relative viscosity of the PA6 resin is 2.8; the glass fiber is an alkali-free chopped glass fiber with a monofilament diameter of 13 μm; the halogen-free flame retardant is a phosphorus-nitrogen flame retardant, i.e., a compound system of diethyl aluminum hypophosphite ADP and melamine polyphosphate MPP; the laser penetrant A is PA6I; the laser penetrant B is PA6T; the antioxidant is Brüggemann H10; the lubricant is ethylene bis stearic acid amide EBS; the flow agent is SH2303 of Dongguan Sanhe Chemical Co., Ltd.; the toner is prepared from organic three primary color toners, and the toner appears black.

[0038] In Comparative Example 3, the relative viscosity of the PA6 resin is 2.8; the glass fiber is an alkali-free chopped glass fiber with a monofilament diameter of 13 μm; the halogen-free flame retardant is Zhejiang Chuanhua Chemical Halogen-free Flame Retardant 9101-1; the antioxidant is Brüggemann H10; the lubricant is ethylene bis stearic acid amide EBS; the flow agent is SH2303 of Dongguan Sanhe Chemical Co., Ltd.; the color powder is prepared from organic three primary color powders, and the color powder appears black.

[0039] The preparation methods of Examples 1-5 and Comparative Examples 1-3 are as follows:

[0040] PA6 resin, laser penetrant A, laser penetrant B, and color powder are pre-mixed in a high-speed mixer according to a certain proportion, the speed is set to 500r / min, and the mixture is mixed for 2-4min to obtain a mixture, and then antioxidant, lubricant, and flow agent are respectively added to the mixture, the speed is set to 500r / min, and the mixture is mixed for 2-4min to obtain a mixed main material A, and finally the mixed main material A is added to the main feeding hopper of the twin-screw extruder; the halogen-free flame retardant is added to the weight-loss feeding hopper of the second heating zone according to proportion; the glass fiber is added to the weight-loss feeding hopper of the fourth heating zone according to proportion;

[0041] The temperature of each section of the 8 extrusion zones of the twin-screw extruder is set as follows: 200-200°C for zone 1, 230-250°C for zone 2, 230-250°C for zone 3, 230-240°C for zone 4, 230-250°C for zone 5, 230-240°C for zone 6, 220-230°C for zone 7, 220-230°C for zone 8 and 230-250°C for die head; the main engine speed of the twin-screw extruder is set at 300-400r / min, auxiliary vacuum systems are set in zones 3 and 6, and the vacuum degrees of the auxiliary vacuum systems are set higher than 0.06Mpa. After the extruded material strips are cooled, pelletized and dried to obtain the finished products.

[0042] The materials prepared in the above Examples 1-5 and Comparative Examples 1-3 were subjected to performance tests, including tensile strength, flexural strength, impact strength, flame retardancy, light transmittance, and molding cycle. The test results are shown in Table 2 below:

[0043] Table 2 Performance test results of the materials prepared in Examples 1-5 and Comparisons 1-3

[0044]

[0045] As can be seen from Table 2 above, and from Examples 1-3, it can be seen that with the increase in the content of laser translucent agent A, on the one hand, the laser transmittance continues to increase; on the other hand, the molding cycle is significantly extended, and even a cooling time of 50s still cannot be completely finalized, and qualified samples cannot be produced, and there is no practical application value. Example 4 and Example 5 compare Example 3 and find that by replacing laser translucent agent A with 3-5 parts of laser translucent agent B, the molding cycle is greatly shortened under the premise that the laser transmittance is almost not reduced, which can meet the actual processing. Comparative Example 1 shows that carbon black greatly affects the laser transmittance of the material. Comparative Example 2 shows that the use of conventional halogen-free flame retardants will greatly weaken the laser transmittance of the material. The present invention uses an organic phosphorus flame retardant with a special structure, which has no obvious effect on the laser transmittance of the material. Comparative Example 2 is compared with Comparative Example 3 to show that the transmittance of Comparative Example 3, which does not contain laser penetrant A, is significantly reduced. The present invention optimizes the aspect ratio of the twin-screw extruder and adopts zoned weightless feeding, avoiding the weakening of the mechanical properties and flame retardancy of the material due to uneven proportions of the components in the centralized feeding and poor mixing effect. The zoned devolatilization of the double vacuum maximizes the laser transmittance of the material. The optimized process route combined with the formula optimization of each embodiment can obtain a glass fiber reinforced halogen-free flame-retardant laser welding PA6 material with high laser transmittance and excellent mechanical properties.

Claims

1. A laser weldable high blackness halogen-free flame-retardant glass fiber reinforced PA6 material, characterized in that: The invention comprises the following components in percentage by weight: PA6 resin 26.9-45.4%, glass fiber 25-35%, halogen-free flame retardant 16-18%, laser penetrant A 10-20%, laser penetrant B 3-5%, antioxidant 0.1-0.3%, lubricant 0.5-0.6%, flow agent 0.4-0.6%, toner 0.2-2%; the sum of the percentage by weight of the above components is 100%; The relative viscosity of the PA6 resin is 2.0-2.8; The glass fiber is an alkali-free chopped glass fiber with a single filament diameter of 7-15 μm; The halogen-free flame retardant is an organic phosphorus flame retardant; the organic phosphorus flame retardant is a composite flame retardant composed of diethyl aluminum hypophosphite and polyaluminum phosphite; The laser penetrant A is PA6I; the laser penetrant B is PA6T; The antioxidant is at least one of a hindered phenol antioxidant, a phosphite antioxidant, an inorganic phosphate antioxidant, and an organic copper salt antioxidant; The lubricant is at least one of stearates, silicones, and ethylene bis stearamides; The flow agent is at least one of low molecular weight polyethylene wax and hyperbranched polyester; The toner is prepared by mixing organic three primary color toners, and the toner appears black.

2. The laser-weldable high-blackness halogen-free flame-retardant glass fiber reinforced PA6 material according to claim 1, characterized in that: The relative viscosity of the PA6 resin is 2.

8.

3. A laser-weldable high-blackness halogen-free flame-retardant glass fiber reinforced PA6 material according to claim 1 or 2, characterized in that: The glass fiber is an alkali-free chopped glass fiber with a single fiber diameter of 13 μm.

4. The laser-weldable high-blackness halogen-free flame-retardant glass fiber reinforced PA6 material according to claim 1 or 2, characterized in that: The antioxidant is an inorganic phosphate antioxidant; the antioxidant is Brueggemann H10.

5. The laser-weldable high-blackness halogen-free flame-retardant glass fiber reinforced PA6 material according to claim 1 or 2, characterized in that: The lubricant is ethylene bis stearic acid amide.

6. The method for preparing a laser-weldable high-blackness halogen-free flame-retardant glass fiber reinforced PA6 material according to claim 1, characterized in that: The following steps are involved: (1) Prepare the raw materials according to the following components: PA6 resin 26.9-45.4%, glass fiber 25-35%, halogen-free flame retardant 16-18%, laser penetrant A 10-20%, laser penetrant B 3-5%, antioxidant 0.1-0.3%, lubricant 0.5-0.6%, flow agent 0.4-0.6%, color powder 0.2-2%; (2) PA6 resin, laser penetrant A, laser penetrant B, and color powder are pre-mixed in a high-speed mixer according to a certain proportion, the speed is set to 500 r / min, and the mixture is mixed for 2-4 minutes to obtain a mixture, and then antioxidant, lubricant, and flow agent are respectively added to the mixture, the speed is set to 500 r / min, and the mixture is mixed for 2-4 minutes to obtain a mixed main material A, and finally the mixed main material A is added to the main feeding hopper of the twin-screw extruder; the halogen-free flame retardant is added to the weight-loss feeding hopper of the second heating zone according to a proportion; and the glass fiber is added to the weight-loss feeding hopper of the fourth heating zone according to a proportion; (3) Set the temperature of each section of the 8 extrusion zones of the twin-screw extruder: zone 1 200-200°C, zone 2 230-250°C, zone 3 230-250°C, zone 4 230-240°C, zone 5 230-250°C, zone 6 230-240°C, zone 7 220-230°C, zone 8 220-230°C, and die head 230-250°C; set the main engine speed of the twin-screw extruder to 300-400r / min, zones 3 and 6 are both equipped with auxiliary vacuum systems, and the vacuum degree of the auxiliary vacuum systems is set to be higher than 0.06Mpa. After the extruded material strips are cooled, pelletized, and dried to obtain the finished product.

7. The method for preparing a laser-weldable high-blackness halogen-free flame-retardant glass fiber reinforced PA6 material according to claim 6, characterized in that: In step (2), the screw length-to-diameter ratio of the twin-screw extruder is (35-42):1.

Citation Information

Patent Citations

  • Black glass fiber reinforced nylon 6 material for laser welding and preparing method thereof

    CN106317864A

  • Color-selectable nylon composite material for laser welding and preparation method thereof

    CN111138849A

  • Semi-aromatic polyamide composition as well as preparation method and application thereof

    CN112574557A